Integrasi Literasi Matematika dan Sains dalam Pendidikan Berbasis Teknologi Digital: Penelitian - Aisyah, Nurul; Firdaus, Firdaus; Prasetyo, Nanda David; Kristiningrum, Kristiningrum; Purba, Christina; Isnaeni, Nurul; Susanti, Sri; Damayanti, Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the integration of mathematics and science literacy in the context of digital technology-based education as an effort to answer the challenges of the 21st century. The method used is Systematic Literature Review (SLR) by examining 45 relevant national and international articles published between 2016–2025. The results of the study show that the use of digital technology such as virtual labs, augmented reality, learning management systems, and interactive media is able to improve students' conceptual understanding, numeracy literacy, and science literacy. The integration of STEAM and Project Based Learning approaches has proven to be effective in developing students' critical, creative, collaborative, and communication skills. In addition, teachers' digital literacy has an important role in the successful implementation of technology-based learning. However, the main challenges still arise in the aspect of infrastructure readiness, the gap in technology access between regions, and the uneven digital competence of educators. This research recommends strengthening teachers' digital competencies, developing an integrative mathematics-science-ICT curriculum, and collaboration between policy stakeholders to create an adaptive and globally competitive learning ecosystem.